Place du Pharmacien d’Officine dans la Prise en Charge des Cancers - HENNOUS , Amira; AFFOUN , Lydia; HASNAOUI , Soundesse; TOUATI , Safa Maroua; GHENNAM , Ahlem (Encadrant) (Université Sétif1 Ferhat Abbas. Faculté de Médecine. Département de Pharmacie, 2024)
Introduction: Cancer is a major public health problem. Strategies to combat and prevent this disease are now a priority in the health policies of many countries. The aim of this study is to clarify the role of the dispensing pharmacist in the screening, prevention and therapeutic education of cancers patients. Materials and methods: two observational surveys using two questionnaires, the first aimed at cancer patients and the second at dispensing pharmacists, were carried out. Data were processed using SPSS. Results: The first investigation included 89 dispensing pharmacists, the majority of whom were women. The majority of pharmacists gave advice on drug administration and were actively involved in the management of adverse effects. Almost half of pharmacists confirmed that they regularly collaborate with other healthcare professionals. The second investigation included 99 cancer patients of all ages, residing nationwide. The sample was almost equally divided between the sexes. The majority of patients expressed great satisfaction with the support they received. Discussion and conclusion: The dispensing pharmacist occupies an important position in the healthcare system, especially in the care of cancers patients. Finally, it is preferable to reinforce pharmacists' skills and keep them up to date with the latest scientific and therapeutic advances in the field of oncology.
Keywords: Pharmacien d'officine; Patient cancéreux; Rise en charge; Education thérapeutique.